Beneath and beyond the Chinese miracle - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
China’s rapid economic progress from an impoverished communist state to the world’s second largest economy within just three decades has enthralled many economists. That the country shifted from the classical centrally-planned command economy to one espousing free market practices while maintaining communist rule, has all given rise to this question: What exactly is the China model? Is it the hybrid of innovative state ownership and tight political control? Or is the rapid growth the result of liberal economic and political reforms?